Pengaruh Kepemimpinan Partisipatif, Religiusitas, Kecerdasan Spiritual, dan Komitmen Kerja Terhadap Kinerja Guru di Sekolah Swasta Katolik Santo Yoseph Denpasar - Mumpuni Mumpuni; Anak Agung Gede Agung; Basilius Redan Werang (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to explain and describe the positive and significant influence of participative leadership, religiosity, spiritual intelligence, and organizational commitment together on teacher performance at the Saint Yoseph Catholic Private School, Denpasar. The type of research used is quantitative research with a causal associative research strategy. Data analysis used in this study is a partial significant test (t-test) and a simultaneous significant test (F-test). The results of this study are that participatory leadership has a partial positive effect on teacher performance at the Saint Yoseph Catholic Private School, Denpasar. This is evidenced by the t-count value of 3.294> 1.98 and a significance value of 0.001 <0.05. Religiosity has a partial positive effect on Teacher Performance at the Saint Yoseph Catholic Private School, Denpasar. This is evidenced by the t-count value of 3.160> 1.98 and a significance value of 0.002 <0.05. Spiritual Intelligence has a partial positive effect on Teacher Performance at the Saint Joseph Catholic Private School, Denpasar. This is evidenced by the t-test value of 3.799 > 1.98 and the significance value of 0.000 < 0.05. Work Commitment has a partial positive effect on Teacher Performance at the Saint Joseph Catholic Private School, Denpasar. This is evidenced by the t-test value of 2.127 > 1.98 and the significance value of 0.036 < 0.05. The study found that all hypotheses in this study have been proven significantly. Participatory leadership, religiosity, spiritual intelligence, and work commitment have a positive and significant effect on teacher performance. The variable that has the greatest influence on teacher performance at the Saint Joseph Catholic Private School, Denpasar is spiritual intelligence. The implication of this study is that participatory leadership, religiosity, spiritual intelligence, and work commitment have an equally important role both individually and together in improving teacher performance.